Global radiant flux from active volcanoes: the 2000–2019 MIROVA database - Coppola, D.; Cardone, D.; Laiolo, M.; Aveni, S.; Campus, A.; Massimetti, F. (Frontiers in Earth Science, 2023)
Since 2000, the Moderate Resolution Imaging Spectroradiometer (MODIS) has acquired infrared images of the Earth's surface daily. These data have made it possible to measure the thermal energy radiated by the world's most famous volcanoes and also to discover and track eruptions at remote and poorly monitored volcanoes. In this work, we present the database of Volcanic Radiative Power (VRP, in W) time series, recorded by the MIROVA (Middle Infrared Observation of Volcanic Activity) system over two decades of MODIS observations (2000-2019) at 111 active volcanoes. The database reveals that globally, the number of thermally active volcanoes each year varies between 60 and 80, almost equally partitioned between volcanoes with a basic (50%) and intermediate (45%) composition, while only 5% is represented by volcanoes erupting acidic lavas. Within the investigated period, the global-scale heat flux was almost stationary, and occasionally punctuated by peaks associated with the largest effusive eruptions (e.g. Bardarbunga and Kilauea). The Volcanic Radiative Energy (VRE, in J) emitted by basic volcanoes (1.8 x 1018 J) in twenty years constitutes 91% of the total, while intermediates and acids contribute only 8% (1.8 x 1017 J) and 1% (1.7 x 1016 J), respectively. A comparison with the volume of lava erupted effusively by the same volcanoes reveals that this difference is attributed to the lower efficiency in radiating thermal energy of increasingly acidic (viscous) lava bodies. Each compositional group is associated with a specific relationship between VRE and erupted volume which characterises most of the effusive volcanoes. On the other hand, some open-vent volcanoes reveal that much more heat is released than that theoretically radiated by the erupted lava. This imbalance (hereby called excess radiation) is attributed to an additional heat source, likely associated with an underlying convective magma column and/or to outgassing through a permeable conduit. We are convinced that the database presented in this work will be useful to support new emerging studies on global-scale volcanism and will contribute to a better understanding of each volcanic system.